Effect of Pot Size in Soil Heat Transfer - Mohamad Fariz, Mohamed Nasir*; Hii, Tuong Sing; Abdul Rahim, Mat Sarip; Muhammad Izzat Nor, Ma'arof; Girma, Tadesse Chala (INTI International University, 2022)
Climate change occurring globally has caused many effects in the current world, such as the rise of sea level, unstable weather, and rise of temperature. Agriculture is among the sector that is affected and since the past few decades’ methods such as controlled environment greenhouses and the hydroponic cultivation has become an alternative to outdoor farming due to the benefits of increased yield and higher efficiency. This study shows that greenhouses design requires various cooling methods such as shading, venting, evaporative cooling, and soil cooling. The soil cooling provide a heat transfer analysis of soil cooling in different pot size and design to contribute related data to encourage further studies. Simulations of a soil cooling system repeated with different pot size under different parameters were conducted; the simulation results were validated and verified with mathematical models and existing data. It is found that smaller pot size has a higher rate of heat conduction in soil due to its higher surface to volume ratio.